Effects of supplemented diets on the growth performance and nutrient contents of gulsha tengra, Mystus cavasius - Fatema, Kaniz; Islam, Md Farukul; Sultana, Nahid; Saha, Badhan (Bangladesh Journal of Zoology, 2017)
To evaluate the effects of two diets on the growth performance and nutrient contents of gulsha, Mystus cavasius was conducted. Growth performance of gulsha was found maximum in rice bran and spirulina feed (treatment T1) and the lowest was observed in commercial feed (treatment T2). Specific growth rate of gulsha was higher in treatment T1 than treatment T2. Treatment T1 had the best proximate composition (moisture 77.28%, ash 3.45%, lipid 4.31% and protein content 15.05%) and nutrient contents (calcium 115.6 mg/100g, phosphorous 166.7 mg/100g, potassium 207.23 mg/100g, magnesium 25.97 mg/100g, iron 1.85 mg/100g and manganese 0.23mg/100g). Therefore, it was found to be better option to produce healthy fish for human consumption. Bangladesh J. Zool. 45(1): 61-71, 2017